2021
DOI: 10.1515/jcim-2020-0507
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effectiveness of mother’s live lullaby and recorded lullaby on physiological responses and sleep of preterm infants: a clinical trial study

Abstract: Objectives Environmental stimuli in neonatal intensive care units can disrupt the physiological stability and sleep of infants. It is essential to perform nursing interventions to reduce the adverse effects of such stimuli. This study aimed to compare the effect of recorded lullabies and mothers’ live lullabies on physiological responses and sleep duration of preterm infants. Methods This study was a randomized clinical trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
5
0
3
Order By: Relevance
“…Overall, MT is known to stabilize physiological parameters by relieving environmental and psychological stress and soothing sympathetic nervous system activity ( 43 , 45 ). Nevertheless, several previous studies have reported inconsistent results, such as not significantly improving physiological parameters after MT ( 25 , 33 ), or improving only some of the various physiological measurement variables measured ( 23 , 27 , 28 ). In contrast, this study showed that all four physiological variables–heart rate, blood pressure, respiratory rate, and oxygen saturation– were consistently stabilized after the intervention.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Overall, MT is known to stabilize physiological parameters by relieving environmental and psychological stress and soothing sympathetic nervous system activity ( 43 , 45 ). Nevertheless, several previous studies have reported inconsistent results, such as not significantly improving physiological parameters after MT ( 25 , 33 ), or improving only some of the various physiological measurement variables measured ( 23 , 27 , 28 ). In contrast, this study showed that all four physiological variables–heart rate, blood pressure, respiratory rate, and oxygen saturation– were consistently stabilized after the intervention.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, a mother's lullaby promotes emotional stability and infant development, and helps to forge a bond with the mother ( 31 , 32 ). However, the effect of mother's lullaby on the physiological homeostasis of premature infants is still controversy ( 33 ), and studies on the effect of the lullaby on the feeding volume and body weight of the infants are lacking. Both feeding vloume and body weight are associated with growth and ultimately the development of premature infants ( 34 36 ).…”
Section: Introductionmentioning
confidence: 99%
“…The birth of premature infants disrupts family activities and plans. It leads to inadequacy in the mother in caring for the baby and reduces the mother's self-esteem [ 37 ]. Aklechi and Mehri (2012) showed that low self-esteem causes feelings of inadequacy, loneliness, and decreased performance [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Portanto, a prematuridade é um problema de saúde pública mundial (LIAO et al, 2018). O nascimento prematuro é a principal causa de mortalidade infantil no primeiro mês de vida, apresentando baixas taxas de sobrevivência em regiões de baixa renda (YUE et al, 2021;NAMJOO et al, 2022).…”
Section: Introductionunclassified
“…Quando o parto ocorre com menos de 37 semanas completas, já é caracterizado como parto prematuro. As subcategorias têm como base a idade gestacional: prematuro extremo (menos de 28 semanas), muito prematuro (28-32 semanas) e prematuro moderado a tardio (32-37 semanas) (YUE et al, 2021;NAMJOO et al, 2022). Esses bebês podem apresentar diferentes formas de deficiência a longo prazo, incluindo dificuldades de aprendizagem, problemas visuais e auditivos, problemas socioemocionais e comportamentais (ALMEIDA et al, 2020;YUE et al, 2021;KEHL et al, 2021).…”
Section: Introductionunclassified